Redesain Website Fakultas dan Pengujian User Experience dengan Menggunakan UEQ-S - Ridwan Maulana Subekti; Mia Kamayani (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The UHAMKA Faculty of Industrial Technology and Informatics website is an information system in obtaining various information about lectures and the faculty. Students can see what information is on the website to make the necessary letters for lecture purposes. The information that appears on the website should make it easier for students and prospective students of the FTII to get the information they want. Students still use WhatsApp groups as a center for lecture and other information. Therefore, it is necessary to redesign the UI / UX website of the FTII UHAMKA with the aim of increasing efficiency and effectiveness in delivering information. This research uses the design thinking method as an approach to website design, problem analysis and needs analysis. The final result of this research is a prototype design of the UHAMKA Faculty of Engineering website with user experience analysis using the User Experience Questionnaire Short version (UEQ-S). The UEQ-S score of the prototype states a pragmatic quality value of 1,250 and a hedonic quality value of 1,167 with an overall value of 1,208.  When compared to the UEQ-S score on the faculty website which gets a pragmatic quality value of 0.569 and a hedonic value of 0.278 with an overall value of 0.424, there is a significant increase in the overall UEQ-S score from the prototype which is 0.784